2010
DOI: 10.1111/j.1600-0684.2010.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fasting on hematologic and clinical chemical values in cynomolgus monkeys (Macaca fascicularis)

Abstract: These results suggested that clinical pathology data would vary after fasting. The decision to feed or fast before blood collection for clinical pathology tests should be made based on careful consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Due to the housing conditions, we were able to assure that all monkeys were strictly fasted overnight, because food remains were retrieved after the last feeding schedule. Although it has been previously reported that fasting is not an absolute prerequisite in hematology [21], it could be clinically relevant in monkeys if the fasting duration exceeds 16 h [22]. Therefore, about 16-h fasting duration used in this study might be clinically relevant reference values for NHPs.…”
Section: Discussionmentioning
confidence: 89%
“…Due to the housing conditions, we were able to assure that all monkeys were strictly fasted overnight, because food remains were retrieved after the last feeding schedule. Although it has been previously reported that fasting is not an absolute prerequisite in hematology [21], it could be clinically relevant in monkeys if the fasting duration exceeds 16 h [22]. Therefore, about 16-h fasting duration used in this study might be clinically relevant reference values for NHPs.…”
Section: Discussionmentioning
confidence: 89%
“…Intra- and inter-study difference in nonhuman primates were known to more variable compare to rodent species. The variables that may account for inter-study variations in cynomolgus monkey include age, sex, geographic origin, presence/absence of anesthetics, fasting, and gravity [ 6 7 8 9 10 11 ]. In addition, analytical instruments, reagents, and methods are variables that could influence the values obtained for a particular parameter, particularly in serum chemistry analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, this should have had little effect on the results obtained. Fasting is not an absolute prerequisite in hematology, and to our knowledge, unless the fasting duration exceeds 16 hours, it has no clinically relevant effects in rats or monkeys .…”
Section: Discussionmentioning
confidence: 96%